A Tale of Two Objectives: The challenge of meeting diverse targets in UK Business Schools - Wolstencroft, Peter; Whitfield, Elizabeth; Dinning, Track (PRISM: Casting New Light on Learning, Theory and Practice, 2023)
Business Schools in Great Britain are currently facing a number of major challenge due to the conflicting objectives that need to be met. The movement towards a metric-driven, performative approach that has occurred in the last decade has meant that the need to meet set measures that focus on the outcomes of students’ study have become imperative. However, focusing solely on these outcomes neglects a second set of objectives that relate to the journey students take during their studies. The need to ensure that both the process and the outcome of students’ studies are stressed is particularly challenging in British Business Schools which are often characterised by a large and diverse student and staff population. This think piece posits that by using a loose/tight cultural approach alongside a Schrödinger’s leadership style, leaders can mitigate some of the challenges that are currently faced in the sector.